PENGARUH RETURN ON SALES DAN RETURN ON ASSETS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2024 - Agil Caturiyan; Randhy Agusentoso (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect to return on sales, return on assets and financial distress on pharmaceutical companies listed on the Indonesia Stock Exchange purposive sampling with the number of selected samples being four companies, namely PT. Kalbe Farma Tbk (KLBF), PT. Industri Jamu dan Farmasi Sido Muncul Tbk (SIDO), PT. Tempo Scan Pacific Tbk (TSPC), PT. Soho Global Health Tbk (SOHO). The method used in this research is a descriptive associative method with a quantitative approach. Data collection used documentation study method, literature study, library research, and the internet. The analysis technique used is panel data test (CEM FEM, REM), classical assumption test, coefficient of determination, t test, f test. The results of the panel data test indicate that the study used the FEM method. The results of the f test show that Fcount>Ftable or 87.86273> 3.467 and the level of significance of the t-prob is 0.0038 <0.05 ttable (3.326> 1.725) or the level of significance of the t-prob is 0.0004 <0.05 ttable (4.305> 1.725), meaning that return on sales and return on assets have a significant effect on financial distress in Pharmaceutical Companies listed on the Indonesia Stock Exchange for the period 2019-2024.